Collaboration of Stakeholders and AI in The Implementation of New Public Service in The Digital Era - Faruq, M.; Wardiyanto , Bintoro; Umpain, Siti Hatijah; Toyib, Muchammad (Golden Ratio of Human Resource Management, 2025)
This study emphasizes the importance of applying the New Public Service (NPS) concept in public service management in the digital era through a Systematic Literature Review (SLR) of five articles from Scopus (2021-2024). The analysis indicates that NPS can enhance the quality of public services in an inclusive, collaborative, and responsive manner. NPS promotes stakeholder collaboration, AI integration in services, and citizen involvement in public value creation. The main challenges in implementing NPS are bureaucratic cultural resistance and insufficient policy dissemination. This study underscores the need for leaders to develop strong commitment, improve effective communication, strengthen cross-sector collaboration, and involve the community in the transition towards NPS. Furthermore, the research highlights the necessity of an integrated public service ecosystem framework to facilitate collaboration among the government, private sector, and society, providing innovative solutions to public service challenges in the digital era.